How the Grddhi Griya Concept Moderates Profit Growth in Village Credit Institutions? - Putu Ayu Anggya Agustina; Elisabeth Ria Viana Praningtyas; Rini Subekti (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study investigates how the Wrddhi Griya concept moderates the relationship between financial performance and profit growth in Village Credit Institutions (VCIs) in Badung Regency, Bali. Rather than being treated as a directly measurable variable, the Wrddhi Griya concept is conceptualized as a cultural and ethical framework whose values are operationalized through lending practices reflected in credit interest income and credit quality. The study employs annual panel data from 122 VCIs covering the period 2016–2023, resulting in 832 observations selected using purposive sampling. Data were analyzed using Moderated Regression Analysis (MRA) with a Fixed Effects Model. The findings reveal that credit interest income and credit quality have positive and significant effects on profit growth. Furthermore, the interaction between profitability and credit interest income is statistically significant, indicating that financial practices reflecting the values of the Wrddhi Griya concept strengthen the relationship between profitability and profit growth. Conversely, the interaction between profitability and credit quality is not statistically significant, suggesting that not all financial practices associated with the Wrddhi Griya concept provide the same moderating effect. These findings demonstrate that local wisdom can complement conventional financial management by encouraging ethical lending practices while maintaining institutional sustainability. This study contributes to the accounting and microfinance literature by integrating indigenous cultural values into the analysis of financial performance in customary-based microfinance institutions